Makna Pernikahan, Perceraian dan Pernikahan Kembali Menurut Matius 19: 1-12 Bagi Orang Percaya Masa Kini - Setiadi, Hendra (PNEUMATIKOS: Jurnal Teologi Kependetaan, 2025)
Marriage in Christianity is sacred and holy because God Himself created humans and made one flesh in a marriage, God wants a marriage that is monogamous as a picture of Monotheism.Divorce in Christianity is not permitted for any reason except death that separates because what God has joined together must not be separated by humans and God hates divorce.Remarriage is common for people in the world who experience failure in their households and want to rebuild their families, but what about Christians, do they allow remarriage?The author in writing this article uses a qualitative descriptive research method, namely using library research in English called library research which uses sources such as articles and books as reference sources in writing articles in order to obtain objective results. The author also conducts scientific research such as thinking empirically and rationally and also doing it systematically.The conclusion is that marriage is sacred and holy and God Himself unites them so that they cannot be divorced for any reason except death that separates and remarriage can only be done by those who are divorced by death.